The impact of species and cell type on the nanosafety profile of iron oxide nanoparticles in neural cells. Issue 1 (December 2016) - Joris, Freya; Valdepérez, Daniel; Pelaz, Beatriz; Soenen, Stefaan; Manshian, Bella; Parak, Wolfgang; De Smedt, Stefaan; Raemdonck, Koen
Abstract Background While nanotechnology is advancing rapidly, nanosafety tends to lag behind since general mechanistic insights into cell-nanoparticle (NP) interactions remain rare. To tackle this issue, standardization of nanosafety assessment is imperative. In this regard, we believe that the cell type selection should not be overlooked since the applicability of cell lines could be questioned given their altered phenotype. Hence, we evaluated the impact of the cell type on in vitro nanosafety evaluations in a human and murine neuroblastoma cell line, neural progenitor cell line and in neural stem cells. Acute toxicity was evaluated for gold, silver and iron oxide (IO)NPs, and the latter were additionally subjected to a multiparametric analysis to assess sublethal effects. Results The stem cells and murine neuroblastoma cell line respectively showed most and least acute cytotoxicity. Using high content imaging, we observed cell type- and species-specific responses to the IONPs on the level of reactive oxygen species production, calcium homeostasis, mitochondrial integrity and cell morphology, indicating that cellular homeostasis is impaired in distinct ways. Conclusions Our data reveal cell type-specific toxicity profiles and demonstrate that a single cell line or toxicity end point will not provide sufficient information on in vitro nanosafety. We propose to identify a set of standard cell lines for screening purposes and to select cell types for detailed nanosafety studies based on the intended application and/or expected exposure.